PECULIARITIES OF THE FORMATION OF IMAGINATION AND CONCEPTS OF NATURE IN CHILDREN - Hamroqulova Dilnavoz Fayzievna (Web of Journals Publishing, 2025)
Today's life itself confirms that the problem of studying man, educating him, providing him with special service, which is considered the highest diversity in the world, has manifested itself in relation to the scale of specific objective and subjective possibilities from the beginning of the emergence of humanity to the end. For while it is clear that it is possible to know a person and have an adequate influence on his external (real) and inner (ideal) world, and through these influences to control him, it is also necessary to pay special attention to the interplay of various social, economic, political, ideological and spiritual interests in this process. Because human development and activism are determined primarily by factors that affect his social interests, ideological views, socio-intellectual potential. Moreover, the formation of a person and the successful functioning of the systems serving him are a derivative of socio-economic, scientific and practical reforms in the country.